Evaluation of changes in the characteristics of motor oils on the Fourier infrared spectrometer - Korneev, S. V.; Zhigadlo, A. P.; Bakulina, V. D.; Pashukevich, S. V. (AIP conference proceedings, 2023)
The results of studies of model contaminated diesel fuels of motor oils produced by the Lukoil company and having various basic bases are presented. The aim of the study is to evaluate the change in the characteristics of oxidized engine oil with different diesel fuel content on a Fourier infrared spectrometer. The study subject is mineral motor oil Lukoil Standard 10W-40, synthetic motor oil Lukoil Lux 5W-40, and semi-synthetic motor oil Lukoil Super 10W-40. Hydrotreated summer diesel fuel with a sulfur content of up to 10 ppm was used as a pollutant. For the test, 7 samples of mineral, 7 samples of synthetic and 7 samples of semi-synthetic motor oils were taken. Oxidation of samples of fresh and contaminated motor oils was carried out using an apparatus for determining the stability of oils against oxidation APSM-1. Then the characteristics of samples of fresh and oxidized motor oils were evaluated on a Spectrum Two FT-IR spectrometer manufactured by PerkinElmer Inc., USA. This FTIR spectrometer is equipped with a specialized cuvette for solving problems in the analysis of lubricating oils. The result of the research is the data on the change in the characteristics of motor oils of different base bases with varying degrees of contamination with diesel fuel. The study can be the basis for developing recommendations for improving the maintenance of internal combustion engines for enterprises that have vehicles with diesel engines at their disposal to increase the resource of power units and reduce operating costs.